Mast Cell Activation, Neuroinflammation, and Tight Junction Protein Derangement in Acute Traumatic Brain Injury. (24th June 2020) - Kempuraj, Duraisamy; Ahmed, Mohammad Ejaz; Selvakumar, Govindhasamy Pushpavathi; Thangavel, Ramasamy; Raikwar, Sudhanshu P.; Zaheer, Smita A.; Iyer, Shankar S.; Burton, Casey; James, Donald; Zaheer, Asgar
Abstract : Traumatic brain injury (TBI) is one of the major health problems worldwide that causes death or permanent disability through primary and secondary damages in the brain. TBI causes primary brain damage and activates glial cells and immune and inflammatory cells, including mast cells in the brain associated with neuroinflammatory responses that cause secondary brain damage. Though the survival rate and the neurological deficiencies have shown significant improvement in many TBI patients with newer therapeutic options, the underlying pathophysiology of TBI-mediated neuroinflammation, neurodegeneration, and cognitive dysfunctions is understudied. In this study, we analyzed mast cells and neuroinflammation in weight drop-induced TBI. We analyzed mast cell activation by toluidine blue staining, serum chemokine C-C motif ligand 2 (CCL2) level by enzyme-linked immunosorbent assay (ELISA), and proteinase-activated receptor-2 (PAR-2), a mast cell and inflammation-associated protein, vascular endothelial growth factor receptor 2 (VEGFR2), and blood-brain barrier tight junction-associated claudin 5 and Zonula occludens-1 (ZO-1) protein expression in the brains of TBI mice. Mast cell activation and its numbers increased in the brains of 24 h and 72 h TBI when compared with sham control brains without TBI. Mouse brains after TBI show increased CCL2, PAR-2, and VEGFR2 expression and derangement of claudin 5 and ZO-1 expression as compared with sham control brains. TBI can cause mast cell activation, neuroinflammation, and derangement of tight junction proteins associated with increased BBB permeability. We suggest that inhibition of mast cell activation can suppress neuroimmune responses and glial cell activation-associated neuroinflammation and neurodegeneration in TBI.